Galaxy–galaxy strong lens perturbations: line-of-sight haloes versus lens subhaloes. Issue 4 (21st March 2022) - He, Qiuhan; Li, Ran; Frenk, Carlos S; Nightingale, James; Cole, Shaun; Amorisco, Nicola C; Massey, Richard; Robertson, Andrew; Etherington, Amy; Amvrosiadis, Aristeidis; Cao, Xiaoyue
ABSTRACT: We rederive the number density of intervening line-of-sight haloes relative to lens subhaloes in galaxy-galaxy strong lensing observations, where these perturbers can generate detectable image fluctuations. Previous studies have calculated the detection limit of a line-of-sight small-mass dark halo by comparing the lensing deflection angles it would cause, to those caused by a subhalo within the lens. However, this overly simplifies the difference in observational consequences between a subhalo and a line-of-sight halo. Furthermore, it does not take into account degeneracies between an extra subhalo and the uncertain properties of the main lens. More in keeping with analyses of real-world observations, we regard a line-of-sight halo as detectable only if adding it to a smooth model generates a statistically significant improvement in the reconstructed image. We find that the number density of detectable line-of-sight perturbers has been overestimated by as much as a factor of two in the previous literature. For typical lensing geometries and configurations, very deep imaging is sensitive to twice as many line-of-sight perturbers as subhaloes, but moderate depth imaging is sensitive to only slightly more line-of-sight perturbers than subhaloes.